2021
DOI: 10.1038/s41598-021-97645-1
|View full text |Cite
|
Sign up to set email alerts
|

Key factors affecting people’s unwillingness to be confined during the COVID-19 pandemic in Spain: a large-scale population study

Abstract: Population confinements have been one of the most widely adopted non-pharmaceutical interventions (NPIs) implemented by governments across the globe to help contain the spread of the SARS-CoV-2 virus. While confinement measures have been proven to be effective to reduce the number of infections, they entail significant economic and social costs. Thus, different policy makers and social groups have exhibited varying levels of acceptance of this type of measures. In this context, understanding the factors that d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…As depicted in the Figure, the average values are generally stable over time except for a notable decrease in the LSNS-6 scores collected during week 27 (5th to 11th of July, 2021) and an increase in the LSNS-6 scores corresponding to week 38 (20th–26th of September, 2021), which might be due to the return to work and school after the summer holidays. A LOESS curve fit reveals a trend of larger average LSNS-6 scores starting in week 43, which might be reflective of the return to the “new normality” and the emergence of pandemic fatigue in the population 41 .
Figure 2 Average LSNS-6 score by income ( a ) and population ( b ) in thousands, both obtained from the 2020 Spanish official statistics (INE) data according to the participants’ reported postal code.
…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As depicted in the Figure, the average values are generally stable over time except for a notable decrease in the LSNS-6 scores collected during week 27 (5th to 11th of July, 2021) and an increase in the LSNS-6 scores corresponding to week 38 (20th–26th of September, 2021), which might be due to the return to work and school after the summer holidays. A LOESS curve fit reveals a trend of larger average LSNS-6 scores starting in week 43, which might be reflective of the return to the “new normality” and the emergence of pandemic fatigue in the population 41 .
Figure 2 Average LSNS-6 score by income ( a ) and population ( b ) in thousands, both obtained from the 2020 Spanish official statistics (INE) data according to the participants’ reported postal code.
…”
Section: Resultsmentioning
confidence: 97%
“…All methods described in this manuscript were carried out in accordance with relevant guidelines and regulations. The survey instrument was approved by the Ethical Committee of the University Miguel Hernandez, which is called the Office for Responsible Research (OIR), in the context of previous research 40 , 41 . Informed consent was obtained from all subjects who had to confirm being at least 18 years old to be able to participate in the survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study performed in the UK found that the population responded more strongly to depression and anxiety in the early stage of the pandemic [38]. Spain's population showed behavioral changes related to the pandemic period as well [31]. It was found that psychological state plays an important role during pandemics and isolation.…”
Section: Discussionmentioning
confidence: 95%
“…An empirical study [30] showed the relationship between mass media information and worries and connections in the context of an immigration employee workplace. Previous research [31] also has proven population fatigue from being in pandemic isolation. This fatigue is more pronounced among women, especially if the isolation lasts more than six months.…”
Section: Buffering Variables: Relationships and Mutual Influencementioning
confidence: 97%